Water Level Regulation for Eco-social Services Under Climate Change in Erhai Lake Over the Past 68 years in China - Wen, Zihao; Ma, Yiwei; Wang, Hao; Cao, Yu; Yuan, Changbo; Ren, Wenjing; Ni, Leyi; Cai, Qinghua; Xiao, Wen; Fu, Hui; Cao, Te; Zhang, Xiaolin (Frontiers in Environmental Science, 2021)
Water level plays a crucial role in the function and social services of lakes. Studies on historical changes in water level and its eco-social function can give insights into future water conservation and management. In this study, interannual and seasonal changes in the water level of Erhai Lake, were analyzed from 1952 to 2019 to explore water level responses to human activities and climate change. The time series was divided into three distinct periods, i.e., 1952–1971, 1972–2003, and 2004–2019. Results showed that the water level and fluctuation differed among the different time periods, i.e., 1965.8 m and 1.3 m (1952 to 1971), 1964.4 m and 1.9 m (1972 to 2003), and 1965.2 m and 1.2 m (1972 to 2003), respectively. The construction and operation of a hydroelectric power plant along the outlet river significantly decreased the water level and increased fluctuation amplitude in the 1972 to 2003 period. Since 2004, however, following the development of local tourism and associated ecological restoration and beautification of the lake, the water level has remained relatively high, with moderate fluctuation amplitude. In addition, compared to the increase in water level amplitude in response to increased wet season (May to October) precipitation in the 1952–1971 period, response sensitivity increased in the 1972–2003 period, but became non-significant in the 2004–2019 period. In regard to the multi-timescale relationship between water level and precipitation, precipitation decreased by 89 mm in the 2004–2019 period compared with that from 1952 to 1971, and artificial water-level regulation resulted in a time-lag of 2, 3–3.5, and 4 months between water level and precipitation during the 1952–1971, 1972–2003, and 2004–2019 periods, respectively. The eco-social aspects of changes in water level are discussed below, and water level regulation from an ecological perspective is recommended to gain economic returns in the future.